2010
DOI: 10.1186/1756-0500-3-194
|View full text |Cite
|
Sign up to set email alerts
|

The impact of temporal variability of biochemical markers PAPP-A and free β-hCG on the specificity of the first-trimester Down syndrome screening: a Croatian retrospective study

Abstract: BackgroundThe variability of maternal serum biochemical markers for Down syndrome, free β-hCG and PAPP-A can have a different impact on false-positive rates between the 10+0 and 13+6 week of gestation. The study population comprised 2883 unaffected, singleton, spontaneously conceived pregnancies in Croatian women, who delivered apparently healthy child at term. Women were separated in 4 groups, dependently on the gestational week when the analyses of biochemical markers were performed. The concentrations of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Based on our findings, we are not advocating for the use of Astraia or Prisca software. The false-negative diagnosed cases are in accordance with the previously reported rates of false-negative cases in screening [31,32]. Rather, we found that this false negative case did not reflect a correct use of the screening.…”
Section: Discussionsupporting
confidence: 90%
“…Based on our findings, we are not advocating for the use of Astraia or Prisca software. The false-negative diagnosed cases are in accordance with the previously reported rates of false-negative cases in screening [31,32]. Rather, we found that this false negative case did not reflect a correct use of the screening.…”
Section: Discussionsupporting
confidence: 90%